2018
DOI: 10.1097/qad.0000000000001707
|View full text |Cite
|
Sign up to set email alerts
|

Improving postpartum retention in care for women living with HIV in the United States

Abstract: Research findings have consistently demonstrated that women living with HIV in the United States and globally experience declines in medication adherence and retention in care after giving birth. A number of studies have identified factors associated with postpartum retention in care, but the evidence base for interventions to address the problem and close this gap in the HIV care continuum is limited. Furthermore, the majority of studies have been conducted in low-resource or moderate-resource countries and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 51 publications
1
43
0
1
Order By: Relevance
“…The survey revealed that 70% of provider respondents were concerned about post‐partum ART adherence, although this emerged only as a secondary finding in the semi‐structured interviews. Several retrospective cohort U.S. studies demonstrate poor post‐partum retention in care and viral suppression , which represents real‐world scenarios in contrast to the highly supported and well‐resourced breastfeeding clinical trials. The WHO acknowledges this concern and advises skilled counselling and adherence support for post‐partum women .…”
Section: Discussionmentioning
confidence: 99%
“…The survey revealed that 70% of provider respondents were concerned about post‐partum ART adherence, although this emerged only as a secondary finding in the semi‐structured interviews. Several retrospective cohort U.S. studies demonstrate poor post‐partum retention in care and viral suppression , which represents real‐world scenarios in contrast to the highly supported and well‐resourced breastfeeding clinical trials. The WHO acknowledges this concern and advises skilled counselling and adherence support for post‐partum women .…”
Section: Discussionmentioning
confidence: 99%
“…Policies including health care coverage through Medicaid and safety net programs for those without health insurance may be relevant to observed differences, including the relatively higher retention rates observed in New York State and in our cohort. (10,12,24) This study included WLWH living in North Carolina which is disproportionately affected by the HIV epidemic, with high HIV-related morbidity and mortality rates in comparison to other US regions. (25) In response, the North Carolina Division of Public Health has long supported innovative public health programs including early HIV detection and linkage to HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited, the studies conducted in the United States to date suggest that women may not receive optimal HIV care postpartum. (8)(9)(10)(11)(12) Furthermore, postpartum ART adherence may also be lower than ART adherence during pregnancy leading to lower virologic suppression rates following childbirth. (13)(14)(15)(16)(17) The HIV care continuum model describes the stages from HIV testing and diagnosis through HIV RNA suppression, with recent United States estimates suggesting that as few as 30% of people living with HIV (PLWH), and 26% of women living with HIV (WLWH), have undetectable HIV RNA levels.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of association between depression and care continuum outcomes in the perinatal period that we observed is likely due to the support provided by PCM or through PCM initiated linkage to mental health programs or other community resources. Interventions aimed at improving retention and viral suppression of pregnant or postpartum WLWH are lacking (Momplaisir et al, 2018); it is therefore important to note that WLWH who receive intensive PCM do not experience worse outcomes than women with no depression.…”
Section: Discussionmentioning
confidence: 99%
“…Depression can be a strong predictor of non-adherence to antiretroviral therapy (ART) (Ammassari, Antinori, Aloisi, Trotta, & Murri, 2004; Springer, Dushaj, & Azar, 2012) and may contribute to poor maternal outcomes at delivery and postpartum (Alder, Fink, Bitzer, Hösli, & Holzgreve, 2007; Goedhart et al, 2010). Previous studies have shown that WLWH have poor viral suppression at delivery (Momplaisir et al, 2015) and poor retention in HIV care postpartum (Adams, Brady, Michael, Yehia, & Momplaisir, 2015; Momplaisir, Storm, Nkwihoreze, Jayeola, & Jemmott, 2018). The impact of depression on HIV care outcomes during pregnancy and postpartum has not been well described.…”
Section: Introductionmentioning
confidence: 99%